The Governance Measurement of Information System Using Framework COBIT 5 in State-Owned Enterprises Insurance Company - Putra Agustian, Andika; Indah Fianty, Melissa (Publisher Cv. Inara, 2023)
Utilizing better Information Technology (IT) management facilities (good governance) is necessary to enhance the efficiency and effectiveness of information technology in a state-owned social insurance company, aligning with the business strategy and complying with the applicable Ministry of State-Owned Enterprises regulations. Therefore, a periodic assessment of IT governance using the COBIT 5 framework is essential. The assessment is conducted on five processes, which involve identifying company objectives, enterprise goals, IT-related goals, and conducting self-assessment. Based on the conducted assessment, the DSS 01 process obtained a final score of 90.22% and achieved a capability level of 4.51. The DSS 02 process obtained a final score of 91.70% and achieved a capability level of 4.59. The DSS 03 process obtained a final score of 90.30% and achieved a capability level of 4.52. The DSS 04 process obtained a final score of 34.15% and achieved a capability level of 1.71. The DSS 06 process obtained a final score of 91.36% and achieved a capability level of 4.58. In the DSS 01 process, three activity findings were identified, and nine improvement recommendations were provided. In the DSS 02 process, one activity finding was identified, and two improvement recommendations were provided. In the DSS 03 process, two activity findings were identified, and four improvement recommendations were provided. Regarding the DSS 04 process, the relevant division is currently conducting internal discussions to improve the control procedures for information availability management for IT service needs.